Outreach to public health professionals: lessons learned from a collaborative Iowa public health project - Walton, Linda J. (Medical Library Association, 2000)
In 1995, the National Library of Medicine (NLM) and the Public Health Service (PHS) recommended that special attention be given to the information needs of unaffiliated public health professionals. In response, the National Network of Libraries of Medicine (NN/LM) Greater Midwest Region initiated a collaborative outreach program for public health professionals working in rural east and central Iowa. Five public health agencies were provided equipment, training, and support for accessing the Internet. Key factors in the success of this project were: (1) the role of collaborating agencies in the implementation and ongoing success of information access outreach projects; (2) knowledge of the socio-cultural factors that influence the information-seeking habits of project participants (public health professionals); and (3) management of changing or varying technological infrastructures. Working with their funding, personnel from federal, state, and local governments enhanced the information-seeking skills of public health professionals in rural eastern and central Iowa communities.